HIGH-GRADE CALCIUM-SODIUM METASOMATISM AND CORUNDUM FORMATION IN THE PRECAMBRIAN BELOMORIAN MOBILE BELT, KARELIA - Serebryakov N.S.; Rusinov V.L. (My University, 2004)
Study of the Khitoostrov, Varatsk, and other corundum occurrences in kyanite-garnet-biotite plagiogneisses of the Chupa section (Belomorian Mobile Belt) has revealed their association with products of low-alkaline Ca-Na metasomatism characterized by high PT conditions. Similar corundum-bearing rocks, which were also presumably formed during subalkaline metasomatism, are known in Tanzania, India, the United States, and other countries. This paper presents the first results of analysis of the corundum-forming Ca-Na metasomatism.
Keywords: Precambrian; Precambrian; Докембрий